2021
DOI: 10.1530/jme-21-0100
|View full text |Cite
|
Sign up to set email alerts
|

Breast adipose regulation of premenopausal breast epithelial phenotype involves interleukin 10

Abstract: Epidemiological studies inversely associate body mass index (BMI) with breast cancer risk in premenopausal women, but the pathophysiological linkage remains ill-defined. Despite the documented relevance of the ‘local’ environment to breast cancer progression and the well-accepted differences in transcriptome and metabolic properties of anatomically distinct fat depots, specific breast adipose contributions to the proliferative potential of non-diseased breast glandular compartment are not fully understood. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…ME1 increased gene expression of ACACA, which is highly enriched in lipogenic tissues and constitutes the first and rate-limiting step in fatty acid biosynthesis. Given that mammary adipocytes are an important component of the tumor microenvironment in mammary cancers [ 50 ], and since leptin is considered to promote breast cancer [ 19 , 20 ], our results suggest the possible utility of targeting mammary ME1 for breast cancer treatment.…”
Section: Discussionmentioning
confidence: 88%
“…ME1 increased gene expression of ACACA, which is highly enriched in lipogenic tissues and constitutes the first and rate-limiting step in fatty acid biosynthesis. Given that mammary adipocytes are an important component of the tumor microenvironment in mammary cancers [ 50 ], and since leptin is considered to promote breast cancer [ 19 , 20 ], our results suggest the possible utility of targeting mammary ME1 for breast cancer treatment.…”
Section: Discussionmentioning
confidence: 88%
“…Breast adipose tissue is an endocrine organ that secretes adipokines, cytokines, chemokines, and growth factors 17. Women with increased body fat exhibit greater breast inflammation with higher levels of circulating metaboinflammatory factors,11 and greater expression of adipogenic and proinflammatory genes is detected in the breast adipose tissue of obese women compared with non-obese women 18…”
Section: Discussionmentioning
confidence: 99%
“…adipogenic and proinflammatory genes is detected in the breast adipose tissue of obese women compared with nonobese women. 18 Limited available evidence has focused on the association of MD with the metabolic syndrome cluster 10 19-23 rather than individual CVD risk factors. Inconsistencies in the results are noted, likely due to the small number of participants, 10 21 24 inclusion of variable age groups (premenopausal, 22 postmenopausal, 21 or both 19 ), and multiple ethnicities.…”
Section: Original Researchmentioning
confidence: 99%
“…Increased adiposity caused by ovarian hormone deficiency in ovariectomized mice results in enhanced expression of aromatase in mammary adipose tissue mediated by decreased local IL-10. Similarly, Alhallak et al 44 reported that compared to normal weight women, IL-10 and FOXP3+ T regulatory levels in breast adipose tissue of obese premenopausal women were upregulated along with the expression of tumor suppressive markers in breast tissue. In vitro application of IL-10 was shown to promote apoptosis and inhibit proliferation in the mammary epithelial cell lines, MCF10A and HMEC.…”
Section: Tumor Stemness and Carcinogenesis In The Obese Inflammatory ...mentioning
confidence: 93%